Gaya hidup sehat dan kecenderungan kecemasan ibu rumah tangga selama pandemi Covid-19 - Diah Pitaloka; IGAA Noviekayati; Amherstia Pasca Rina (INNER: Journal of Psychological Research, 2022)
Abstract The spread of the Covid-19 virus has caused the number of victims to increase every time. This case causes anxiety, especially for a housewife. Housewives are not only responsible for their household but also think about the health of their families during the pandemic. The purpose of this study was to determine the relationship between a healthy lifestyle and the tendency of housewives to worry during the COVID-19 pandemic in Sidoarjo. This study involved 70 housewives in Sidoarjo. The sampling technique used purposive sampling technique. Based on the results of the analysis of the Spearman-Brown correlation test, a correlation score of 0.78 was obtained with a significant p=0.522 (p>0.005), which means that there is an insignificant positive relationship between a healthy lifestyle and a tendency to anxiety. In other words, the results of this study indicate that there is no relationship between a healthy lifestyle and the tendency of housewives to worry. Through these results, the hypothesis in this study is not accepted. Keywords: Healthy Lifestyle, Anxiety, Housewives